2019
DOI: 10.3390/ani9110858
|View full text |Cite
|
Sign up to set email alerts
|

Association of Twelve Candidate Gene Polymorphisms with the Intramuscular Fat Content and Average Backfat Thickness of Chinese Suhuai Pigs

Abstract: Simple SummaryAppropriate intramuscular fat content (IFC) is the goal of consumers and the direction that breeders must pursue. However, it is difficult to improve the IFC but not average backfat thickness (ABT) by traditional breeding methods, and pigs must be slaughtered to accurately measure IFC. Marker-assisted selection (MAS) provides an economic and efficient method to improve the IFC in pigs. Our research indicated that the FABP3 (rs1110770079) single nucleotide polymorphism (SNP) could be a candidate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
1
20
1
Order By: Relevance
“…The experimental animals were from Huaiyin pig breeding plant in Jiangsu Province, China. Suhuai pig is a synthetic Chinese breed that is derived from Large white pig (75%) and Chinese Huai pig (25%) [13]. A total of 35 Suhuai finishing pigs (158.5 ± 2.0 d) with body weight (BW) of 62.9 ± 0.8 kg were selected and allotted to 5 treatment groups (7 replicates for each treatment) using a randomized complete block design.…”
Section: Experimental Animals and Designmentioning
confidence: 99%
“…The experimental animals were from Huaiyin pig breeding plant in Jiangsu Province, China. Suhuai pig is a synthetic Chinese breed that is derived from Large white pig (75%) and Chinese Huai pig (25%) [13]. A total of 35 Suhuai finishing pigs (158.5 ± 2.0 d) with body weight (BW) of 62.9 ± 0.8 kg were selected and allotted to 5 treatment groups (7 replicates for each treatment) using a randomized complete block design.…”
Section: Experimental Animals and Designmentioning
confidence: 99%
“…We found that the litter size of EHL and MS pigs were significantly higher than that of SH and TPE-L pigs. SH pig population is a unique cultivar possessing ancestries of Chinese Huai pig and British Yorkshire pig [13]. There are only a few related studies on reproductive traits for SH pig breed [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In this research, a total of 10 pig populations including the Eastern Chinese Jianghai pig breeds (EHL, MS and JXH), the Southern Chinese pig breeds (BMX and WZS), Chinese cultivated Suhuai (SH) pigs, which contains approximately 25% Chinese Huai pigs and 75% British Yorkshire pigs ancestries [13], Chinese lean-type Taiwanese Landrace pigs (TPE-L), Western commercial pigs including Canadian Yorkshire (CAN-Y) pigs, American Yorkshire (USA-Y) pigs and French Yorkshire (FRA-Y) pigs were used to study whether the rs339939442 in the AHR gene is polymorphic and associated with the litter size in Chinese and Western pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese Suhuai pig is a newly cultivated breed, which contains approximately 25% Chinese Huai and 75% Large White ancestries. Suhuai pig inherits high tolerance to coarse feed from Chinese Huai pig and high lean meat yield from Large White [17,18]. At present, more than 10,000 Suhuai sows are raised in over 20 provinces in China [18].…”
Section: Introductionmentioning
confidence: 99%
“…Suhuai pig inherits high tolerance to coarse feed from Chinese Huai pig and high lean meat yield from Large White [17,18]. At present, more than 10,000 Suhuai sows are raised in over 20 provinces in China [18]. Since Large White has more RIB and larger CBC than Chinese indigenous pigs, we speculated that there are phenotypic variations of RIB and CBC within Suhuai pig populations.…”
Section: Introductionmentioning
confidence: 99%